The Transitory forms of Lesotho Customs Administration and Tax Revenue Collection Since the Post Independence Era Till the Early 2000s: Strategies, Organizational Structures, Trade Facilitation and Limitations (Global Journal of Human-Social Science, 2015)
In a highly competitive global environment, customs administration plays a vital role in the growth of international trade and development of the globe by facilitating trade among countries. Its role is also essential in expediting the growth of revenue through imports and exports taxation. This requires efficient and effective customs systems and procedures that can significantly influence the economic competitiveness of a nation. Lesotho being a member of Southern African Customs Union (SACU) and World Trade Organization (WTO) has a remarkable history in Customs Administration ('CA'). Overtime CA has been a useful strategy of the government for revenue collection and trade facilitation. The country has also undergone social, economic as well as political transformations which have brought significant changes that affected the revenue base and brought a mismatch between the revenue and expenditure.
Keywords: 1 customs administration/system; 2 lesotho; 3 tax revenue collection reforms; 4 trade; 5 free trade facilitation and limitations 6 colonial form